P-66 Pilot study EPHOR: exploring non-invasive sampling: evaluating quality and stability of dried blood spots, saliva, and urine samples. (14th March 2023) - Ryck, De; Eline, Verscheure; Stierum Rob, H; Vivi, Schlünssen; Mette Lund, Würtz Anne; Manolis, Kogevinas; Harding, Barbara; Broberg, Karin; Shan, Narui; Johanna, Samulin-Erdem; Das Mrinal, K; Makris Konstantinos, C; et al.
Abstract : Introduction: In the European Exposome Project for Health and Occupational Research (EPHOR), a working life exposome toolbox is developed to support evidence-based and cost-effective prevention to improve health at work. Our narrative synthesis showed the potential of using non-invasive sampling for the occupational exposome. This pilot study aims to develop, optimise and validate methods, for collection, storage, detection, and quantification of biomarkers in non-invasive matrices, as alternatives to e.g. whole blood collection via phlebotomy. Materials and Methods: This study was approved by the Ethics Committee Research UZ/KU Leuven (S64599). Nineteen healthy participants were included after filling in informed consent. At two visits to the lab, exhaled breath (EB), EB condensate, lung volumes (spirometry), peripheral blood via phlebotomy, dried blood spots (DBS), saliva and urine were collected and questionnaires were filled in. For a third sampling at home, participants were asked to use instructions for self-sampling of DBS, saliva and urine and bring the samples back to the lab. Each sampling was approximately six months apart. DBS from the first visit and home sampling were stored at room temperature (RT), while those from the second visit were stored at -80° C until analysis. Saliva was collected by chewing a cotton swab for one minute. Results: By comparing biomarkers in samples of the three timepoints within individuals, we will be able to evaluate the stability and quality of non-invasive samples with different storage times and conditions. We will explore the potential of self-sampling, which can ease sampling in large groups of participants, in shift work, remote areas and during pandemics. Conclusion: This pilot study will allow us to investigate the quality and stability of non-invasive samples, as well as their potential usage in research. EPHOR is funded by the European Union's Horizon 2020 research and innovation programme under grant agreement number 874703.